KAJIAN ESTETIKA PAMOR KERIS KAMARDIKAN - Febrian Wisnu Adi Adi (Institut Seni Indonesia Yogyakarta, 2016)
The aim of this research is to be searched about aesthetic and historical background thatincludes the shape, meaning, and function as well as the factors that underlie Pamor keriskamardikan in Surakarta. The analysis of the Pamor keris kamardikan Surakarta is not a simplematter. The question such as: what Pamor keris kamardikan is; why it had been created; whenit start created; whose the man behind of created; where place that Pamor keris kamardikanhas been exsist; and how about the histocal about it. Change of palace culture maybe happento the progresive culture with any perception. It can be indicated like social criticism movementin postmodern age, such as: happening art, environmental art, etc.While the factors underlie the similarities and differences are the internal and externalfactors. The Internal factors are the rules and policy stated by the actor in this regions. Theexternal factor is the factor happens because the society social condition that is more developedas well as the policy of the government of Republic of Indonesia in the tourism sector.The method used in the research is qualitative research with multidicipline approachfocusing on the study of art. Aesthetic approach is used for relating the style of art. Thisapproach is used with other approaches and use the relevant teories such as: history,communication, anthropology, archeology, and sociology.This research has conelude that movemen of Pamor keris kamardikan Surakarta is in thestructure or style. Historical background of movement started on 1970 in case of many kerisartist in Surakarta created it with many purposed, basicly, Pamor keris Kamardikan Surakartahave two poin of movement, there are an aesthetic.Keyword: Pamor keris, kamardikan, aesthetic.